Islamic Values and Javanese Culture as Determinants of Employee Performance: The Mediating Effect of Employee Happiness - Khoiriyyah, Amilatul; Setiawan, Nanang (Proceedings of Annual Conference for Muslim Scholars, 2024)
Islamic values and culture have the potential to enhance employee performance; however, the literature presents inconsistent results and ongoing debates. This study aims to examine how employee happiness mediates the relationship between Islamic values, Javanese culture, and employee performance. The methodology employed in this research is quantitative, with data collected through questionnaires distributed to employees of multinational companies in East Java. A total of 125 respondents participated in this study. The findings indicate that employee happiness significantly mediates the relationship between Islamic values, Javanese culture, and employee performance, where the influence of Islamic values and Javanese culture on performance becomes stronger in the context of happy employees. This research contributes to a deeper understanding of the role of employee happiness in influencing the dynamics between Islamic values, Javanese culture, and employee performance. These findings can serve as a foundation for multinational companies to develop management strategies that are more sensitive to Islamic values and local culture to enhance company performance